Republic of Moldova : Staff Report for the 2012 Article IV Consultation, Fifth Reviews Under the Extended Arrangement and Under the Three-Year Arrangement Under the Extended Credit Facility, and Requests for Waivers for Non-Observance and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2012)
After the 2009 crisis, policies have improved markedly, backed by substantial foreign assistance. Notably, fiscal adjustment has reduced the large budget imbalance, monetary policy has tamed inflation, and structural reforms have spurred strong export expansion. These reforms led to impressive growth in 2010-11, but activity decelerated in 2012, reflecting the slowdown in the EU. The economy is highly exposed to further intensification of the euro area crisis via its dependence on remittances, exports, and capital inflows.